EXPERIMENTAL STUDY OF TURBULENCE IN THE TEST SECTION OF WIND TUNNEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The given report presents an experimental study using PIV methods (Particle Image Velocimetry) of the relative turbulence in the test section of the wind tunnel ULAK-1, located in the Laboratory of Autonomous Aircraft Aerodynamics in the Plovdiv Branch of the Technical University of Sofia. By means of the turbulence sphere method and by analysis of the flow in the test section in two perpendicular planes (parallel to the free-stream velocity and Trefftz plane), the turbulence factor and the relative turbulence were determined. The obtained results are important characteristics of the wind tunnel and will be used in future experimental studies. The same are compared with previous ones obtained by hot-wire anemometry measurements.